2014
DOI: 10.1590/s0100-06832014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Water storage variability in a vineyard soil in the southern highlands of Santa Catarina state

Abstract: SUMMARYIn the subtropical regions of southern Brazil, rainfall distribution is uneven, which results in temporal variability of soil water storage. For grapes, water is generally available in excess and water deficiency occurs only occasionally. Furthermore, on the Southern Plateau of Santa Catarina, there are differences in soil properties, which results in high spatial variability. These two factors affect the composition of wine grapes. Spatio-temporal analyses are therefore useful in the selection of cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
1
0
5
Order By: Relevance
“…Similar results to this study were reported by Comin et al (2013), in which the authors (Comin et al, 2013;Luciano et al, 2014). In contrast to the results found by Arruda et al (2010) and Espanhol et al (2007), but corroborating with those found by Bronick and Lal (2005) and Comin et al (2013), the organic fertilization contributed to the increase of the geometric mean diameter.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results to this study were reported by Comin et al (2013), in which the authors (Comin et al, 2013;Luciano et al, 2014). In contrast to the results found by Arruda et al (2010) and Espanhol et al (2007), but corroborating with those found by Bronick and Lal (2005) and Comin et al (2013), the organic fertilization contributed to the increase of the geometric mean diameter.…”
Section: Resultssupporting
confidence: 92%
“…However, the soil porosity is not the only way to explain the change in soil bulk density. In this way, Bronick e Lal (2005), Luciano et al (2014) and Richart et al (2005) attributed the lowest Bd to the greatest presence of organic material at the superficial layers of the soil, especially when the applications of the organic sources occur superficially without the incorporation to the soil. Moreover, according to Richart et al (2005), this is due to the fact that the organic matter has a density of approximately 2.5 times less than the other constituents of the soil.…”
Section: Resultsmentioning
confidence: 99%
“…The 0.10-0.20 m layer did not affect the test of means, which were equal. Soil mobilisation promoted a decrease in the percentage of micropores to the detriment of macropores, making the soil with lower water holding capacity and gas flow, which could lead to a fast water deficit for crops (Luciano et al, 2014). Moreover, it may also decrease soil moisture, corroborating the results obtained by Oliveira et al (2015).…”
Section: Resultssupporting
confidence: 75%
“…Por isso, um solo com adequada estrutura apresentará agregados estáveis e melhor distribuição de poros e, por consequência, melhor infiltração de água (Schoenholtz et al, 2000). Atributos da estrutura do solo, como a densidade, a macro e microporosidade, a presença e a estabilidade de agregados, e a resistência à penetração (Luciano et al, 2014;Schoenholtz et al, 2000) devem ser mensurados para avaliar como o manejo influencia as características do solo e a relação dele com a planta (Luciano et al, 2014).…”
unclassified